Low frequency noise and photo-enhanced field emission from ultrathin PbBi2Se4 nanosheets - Suryawanshi, Sachin R.; Guin, Satya N.; Chatterjee, Arindom; Kashid, Vikas; More, Mahendra A.; Late, Dattatray J.; Biswas, Kanishka (Journal of Materials Chemistry C, 2016)
Atomically thin two-dimensional layered materials have gained wide interest owing to their novel properties and potential for applications in nanoelectronic and optoelectronic devices. Here, we present the spectral analysis and photo-enhanced field emission studies of a layered intergrowth PbBi2Se4 nanosheet emitter, performed at the base pressure of similar to 1 x 10(-8) mbar. The emitter shows a turn-on field value of similar to 4.80 V mu m(-1), corresponding to an emission current density of similar to 1 mu A cm(-2). Interestingly, when the cathode was illuminated with visible light, it exhibited a lower turn-on field of B3.90 V mm(-1), and a maximum emission current density of similar to 893 mu A cm(-2) has been drawn at an applied electric field of similar to 8.40 V mu m(-1). Furthermore, the photo-enhanced emission current showed reproducible, step-like switching behavior in synchronous with ON-OFF switching of the illumination source. The emission current-time plots reveal excellent stability over a duration of similar to 6 h. Low-frequency noise is a significant limitation for the performance of nanoscale electronic devices. The spectral analysis performed on a Fast Fourier Transform (FFT) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha similar to 0.99. The low frequency noise, photo-enhanced field emission, and reproducible switching behavior characterized with very fast rise and fall times propose the layered PbBi2Se4 nanosheet emitter as a new promising candidate for novel vacuum nano-optoelectronic devices.